The Role of Branched-Chain Amino Acids and Eicosapentaenoic Acid in Improving Body Composition and Functional Capacity in Nasopharyngeal Carcinoma Patients with Cancer Cachexia: A Case Report - K.N, Beta Novianti; Krisadelfa Sutanto; Nurul Ratna Mutu Manikam (HM Publisher, 2024)
Introduction: Cancer cachexia is a debilitating syndrome characterized by involuntary weight loss, muscle wasting, and functional decline, negatively impacting quality of life and survival. Nutritional interventions, including branched-chain amino acids (BCAAs) and eicosapentaenoic acid (EPA), have shown promise in ameliorating cachexia. This case report illustrates the potential benefits of these nutrients in a patient with nasopharyngeal carcinoma. Case presentation: A 65-year-old female presented with severe fatigue, dysphagia, and significant weight loss (11 kg in 6 months) secondary to nasopharyngeal carcinoma (T1N3Mx, stage IV). She was diagnosed with cancer cachexia and severe malnutrition. Nutritional therapy included enteral nutrition with 1.5-2 g/kgBW/day protein, 11-12 g/day BCAAs, and 1-2 g/day EPA. Conclusion: This case report suggests that a nutritional approach combining high protein, BCAAs, and EPA may improve body composition and functional capacity in patients with cancer cachexia. Further research is warranted to confirm these findings in larger studies.